Tokugawa Japan : (University Tokyo Press, 1990)
In sharp contrast to the medieval period which preceded it, the nearly three-hundred-year Tokugawa period, referred to as the Kinsei or early modern period, was marked by a highly organized administrative system and economic development based on an unprecedented level of agricultural productivity. This is the period in which Japan's distinctive culture attained its apex.